Nonlinear Optical Properties of 2D Materials and their Applications - Xie, Zhixiang; Zhao, Tianxiang; Yu, Xuechao; Wang, Junjia (Small (Weinheim an der Bergstrasse, Germany), 2024)
2D materials are a subject of intense research in recent years owing to their exclusive photoelectric properties. With giant nonlinear susceptibility and perfect phase matching, 2D materials have marvelous nonlinear light‐matter interactions. The nonlinear optical properties of 2D materials are of great significance to the design and analysis of applied materials and functional devices. Here, the fundamental of nonlinear optics (NLO) for 2D materials is introduced, and the methods for characterizing and measuring second‐order and third‐order nonlinear susceptibility of 2D materials are reviewed. Furthermore, the theoretical and experimental values of second‐order susceptibility χ(2) and third‐order susceptibility χ(3) are tabulated. Several applications and possible future research directions of second‐harmonic generation (SHG) and third‐harmonic generation (THG) for 2D materials are presented. The nonlinear optical properties of 2D materials are of great significance to the design and analysis of applied materials and functional devices. In this article, a comprehensive review of measurement methods for nonlinear susceptibility is provided. Nonlinear susceptibility of different 2D materials are compared. Their applications in nonlinear photonic devices are discussed.